Experimental study on composite stiffened panel with low velocity impact damage under compressive load. (May 2015) - An, T.; He, Y.; Shao, Q.; Wang, J.
Abstract : Drop hammer impact tests on three typical locations of composite stiffened panel are carried to produce low-velocity impact damage, and then compressive experiments on damaged specimen are conducted to obtain the buckling load and failure load. Test results of damaged specimens and undamaged ones are compared to analyse the effect of damage on the carrying capacity of the structure. The results show that the low-velocity impact damage on the flange of the joist can obviously reduce compressive buckling load and intensity of the structure, while the damage on the other two positions has less influence on the compressive results. Besides, experiment indicates that the damage on the flange will enlarge in failure process. The experimental results offer some valuable references to engineering application of the structure.